Cleaning oil paintings: NMR relaxometry and SPME to evaluate the effects of green solvents and innovative green gels. (15th May 2019) - Prati, S.; Sciutto, G.; Volpi, F.; Rehorn, C.; Vurro, R.; Blümich, B.; Mazzocchetti, L.; Giorgini, L.; Samorì, C.; Galletti, P.; Tagliavini, E.; Mazzeo, R.
Abstract : NMR relaxometry together with SPME allow evaluation of the effects of new green gels for the cleaning of paintings. Abstract : Gels have been recently introduced in conservation to better control the cleaning action. The slow solvent release is of utmost importance to selectively remove varnish layers of a few microns in thickness, applied on paint layers which may have similar chemical properties. To evaluate the interactions of the underlying paint with solvents, diagnostic methods should study the physical and chemical changes that occur during and after the treatment. In this paper, we propose an innovative analytical protocol based on the combination of solid phase microextraction (SPME) and nuclear magnetic resonance (NMR) relaxometry to evaluate solvent entry and retention in the paint layer, as well as the induced microscopic and macroscopic changes to the elasticity of the binder. Moreover, FTIR and optical microscopy are used to evaluate the cleaning efficacy. The proposed analytical protocol can be used to identify solvents or gels which show minimal interaction with the paint. In particular, we have tested the protocol to evaluate the performance of non-toxic and biodegradable green gels on mock-ups and on a painting dated 19th century showing that they perform better than solvents applied with swabs. Five-minute gel treatments were found to be as effective at varnish removal as thirty-second swab treatments following traditional cleaning methods. Cleaning with gels limits the mechanical stress, solvent entry and retention in the paint layer, and reduces the embrittlement due to lower mass transfer. An unusual "sandwich" system was used to avoid the retention of gel residues on the surface with the gels contained in two sheets of Japanese papers – one on top and the other at the bottom.